The Law of Riba Money Is Used For The Hajj Worship - Harahap, Aziddin; Syahputra Harahap, Hasmi; Harahap, Arman (International Journal Of Community Service, 2023)
The purpose of this community service activity is to find out about the Legal Study of Riba Money Used for Hajj Pilgrimage which was presented in the Naharul Ijtima NU (Nahdlatul Ulama) of South Labuhanbatu Regency. This study is also to understand the law of usury money used in pilgrimage so that it has an impact on the lawful or unlawful use of usury money. The assessment method uses participatory methods, lectures and discussions as well as interesting questions and answers. This activity was carried out on July 1 2022 with the number of participants who took part in the study consisting of 35 people located at the NU PC Secretariat Labuhanbatu Selatan. For this reason, through this activity it is possible to increase shared understanding regarding the use of usury money in pilgrimage with studies that say usury is like what the exact conceptual paradigm is. The types of law that are certain are halal and haram. Based on the study it was found that the law of usury money being used for pilgrimage is unlawful. Therefore, an in-depth study must be at the core of what is said to be what usury is like. Riba is additional taking, both in buying and selling transactions and lending and borrowing in vanity or contrary to the principles of muamalah in Islam. For this reason, we hope that this research activity can fortify us not to commit usury, in essence, we do not earn money that is contrary to Islamic law in terms of additional withdrawals, both in buying and selling transactions and lending and borrowing.